2018
DOI: 10.3758/s13414-017-1457-8
|View full text |Cite
|
Sign up to set email alerts
|

Seeing structure: Shape skeletons modulate perceived similarity

Abstract: An intrinsic part of seeing objects is seeing how similar or different they are relative to one another. This experience requires that objects be mentally represented in a common format over which such comparisons can be carried out. What is that representational format? Objects could be compared in terms of their superficial features (e.g., degree of pixel-by-pixel overlap), but a more intriguing possibility is that they are compared on the basis of a deeper structure. One especially promising candidate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…To test more specifically for the role of mid-level texture-like statistical features in the perception of generative processes, we created a new set of twodimensional objects to pit them against Euclidean shape similarity-a prime source of object classification (e.g., Lowet, Firestone, & Scholl, 2018;Wilder, Feldman, & Singh, 2011). As a control, after asking participants to classify the stimuli, we used apparent motion to measure low-level perceptual shape similarity between stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…To test more specifically for the role of mid-level texture-like statistical features in the perception of generative processes, we created a new set of twodimensional objects to pit them against Euclidean shape similarity-a prime source of object classification (e.g., Lowet, Firestone, & Scholl, 2018;Wilder, Feldman, & Singh, 2011). As a control, after asking participants to classify the stimuli, we used apparent motion to measure low-level perceptual shape similarity between stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, behavioral research with humans has shown that participants extract the skeleton of 2D shapes (Firestone & Scholl, 2015;Kovács, Fehér, & Julesz, 1998;Psotka, 1978), even in the presence of border perturbations and illusory contours (Ayzenberg, Chen, Yousif, & Lourenco, 2019). Other research has shown that skeletal models are predictive of human object recognition (Destler, Singh, & Feldman, 2019;Lowet, Firestone, & Scholl, 2018;Wilder, Feldman, & Singh, 2011), even when controlling for other models of vision . Although these studies provide evidence that skeletons are associated with perceptual organization and object recognition, at least when these functions are tested independently, it remains unknown whether shape skeletons are involved in both functions.…”
Section: Introductionmentioning
confidence: 94%
“…Skeletal similarity between every object was calculated in 3D, object-centered, space as the mean Euclidean distance between each point on one skeleton and the closest point on the second skeleton following maximal alignment (see Methods). We chose to test a 3D skeletal description because of behavioral 48 and neural 49 evidence for 3D object-centered representations in the visual system, which include a sensitivity to 3D skeletal structures 36,37 .…”
Section: Experiments 1 -Is Perceived Object Similarity Uniquely Predicmentioning
confidence: 99%